PENGARUH MEDIA SIMULASI KOMPUTER TERHADAP AKTIFITAS DAN KEMAMPUAN MAHASISWA PRODI PTE - Agus Hari Wibowo; Ahsan Muafa; Ina Sunaryantiningsih (IKIP PGRI MADIUN, 2014)
The vocational school graduates are expected to be work-ready but roughly, only half of them have the competency. This may results from vocational teacher's low pedagogical and professional competencies. This research aims at investigating the effects of computer simulation toward electricalengineering pre-service teachers' activeness in learning process and their ability in designing electrical control system. Using quasi-experiment with non equivalent control group pre-test post-test design, the research was conducted in Department of Electrical Engineering Education in IKIP PGRI Madiun. Statistical analysis on pre-test and post-test mean scores of the group shows that there is a significant increase on students' ability in designing electrical control system with sig 0.00. Observation on students' activeness in learning process also indicates increased activeness compared to before the use of media. These findings indicate that computer simulation serves as an effective teaching media to improve students' activeness and competencies and should be encouraged in vocational education.